Estudo Avaliativo de dois cursos de Educação Física no Município de Fortaleza via teoria da gestão da informação e do conhecimento - Dias, Jocyana Cavalcante da Silva (2010)
The purpose of this study is to evaluate management of information and knowledge in two graduate school of physical education: a public institution and a private one. The theoretical base is the Davenport model (1998). The empirical date were collected through a questionnaire and a evaluation scale. The questionnaire aimed to characterize the subjects involved in the research (teachers, students and staff personal). The scale, with 42 items, offered three possible answers: Agree, agree in part and disagree. The scale coefficient of reliability, sensibility, validity, standard error of measurement, and item discrimination were determined. The construct validity was determined using principal components factorial analysis, and orthogonal EQUAMAX rotation. Seven factors were identified (information technology, information politics, information culture, information architecture, information strategy, evaluation of information management, information team), subjacent the construct measured. Through analyses of variance, the general linear model indicated that the sample is different of the subject institution only. No significative discrepancies were observed in relation to sex, age, time in the institution and respondent category. The private institution presented best results than the public one, in all seven factors, specially in the factor technology. It is assumed that the updating with the innovations technology is crucial to the private institutions in the implication of their business and, consequents, their profits.